Snellen Chart Based On Android Control - Annisa Novantina Eka Fitria; Priyambada Cahya Nugraha; Lamidi Lamidi (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2019)
Eye vision is a person's visual acuity examination that is usually done using a snellen chart. Snellen chart is a poster that contains a number of letters that are different on each line with the letters getting closer to the bottom lines. Eye vision examination using a normal snellen chart is done at a distance of 6 meters because someone is considered normal if he is able to read on the 20/20 line in feet or 6/6 in meters. Snellen chart control android is an electronic snellen chart that controls the light transfer using Android. Commands originating from the mitapp application on android are sent to the bluetooth HC-05 module in the minsys Atmega16 circuit. Atmega 16 was chosen because it has a sufficient number of pins to control the displacement of the lights used by 23 lights. The appearance of the mitapp application has been adjusted to the letters contained in the snellen chart, making it easier for operator to correct the results of the readings that have been performed by the eye vision patient.